LED based soil spectroscopy - Mohd. Yusof, Khairunnisa (Laser Center, Universiti Teknologi Malaysia, 2016)
Soil is a medium for plant roots to grow, absorb water and necessary solutes for growth. Soil macronutrient testing is helpful for determining the nutrient content in soil before applying fertilizer for quality and process controls of agricultural productivity and soil fertility. Spectroscopy is an emerging technology which is rapid and simple has been widely used in agricultural and food analysis processes. The capability of spectroscopy to characterize material from the transmission or absorbance has been used in this paper to measure nitrogen ( N ), phosphorus ( P ) and potassium ( K ) content in organic soil. The paper details preliminary characterization of soil spectroscopy with a Deuterium - Halogen lamp and spectrometer to measure the absorbance level of the macronutrients. The extracted nutrients were mixed with the colour reagent and specific colour ed solution was developed. The result shows high absorbance level for N and P are at 970 nm in wavelength. In addition, N gi ve absorbance at wavelength 450 nm and P yield absorbance at 800 nm wavelength . K was measured high at 620 nm. Further experiments were conducted to measure the absorbance characteristic of N , P and K for 20 minute period. The result shows that P and K has constant value of absorbance for 20 minutes duration while N , have stable absorbance value after 10 minutes being illuminated by 470 nm blue light - emitting diode ( LED ) . For future works, the optical measurements will be implemented using visible and near infrared LED and the photodetector in order to replace the spectrometer usage for soil spectroscopy. This would lead to achieve the primary objective of this research in developing a simple and low cost spectroscopy uses LED .